2024
DOI: 10.1021/acsomega.4c00987
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Mechanism and Regeneration Performance of Calcined Zeolites for Hydrogen Sulfide and Its Application

Xianghao Zha,
Feixing Li,
Bo Feng
et al.

Abstract: Hydrogen sulfide (H2S) is a very toxic, acidic, and odorous gas. In this study, a calcined zeolite was used to investigate the adsorption performance of H2S. Among particle size, calcination temperature and time calcination temperature and time had significant effects on the adsorption capacity of H2S on the zeolite. The optimal calcination conditions for the zeolite were 332 °C, 1.8 h, and 10–20 mm size, and the maximum adsorption capacity of H2S was approximately 6219 mg kg–1. Calcination could broaden the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…There was also a linear negative correlation between the removal capacity of ACA-cactus formaldehyde from air ow and working time, with correlation coe cients greater than 0.91 (Table 1). It is well known that air ow rate and pollutant concentration are two important factors to control membrane diffusion, and effective working time is another key material performance index (Zha et al, 2024). In the orthogonal experiment, the formaldehyde concentration (Factor 1) was set at three levels as 0.081, 0.162 and 0.326 mg•m − 3 ;the air ow rate (Factor 2) was set at three levels as 0.5, 1.0 and 2.0 L•min − 1 while the working time (Factor 2) were set at three levels as 5, 10 and 30 h. Results showed that the rapid and highly e cient formaldehyde dissipation of plant active components in ACA-cactus made the air ow rate become the key factor on the removal rate with the sequence of Factor 2 > Factor 3 Factor 1.…”
Section: In Uencing Factors On Removal Ratementioning
confidence: 99%
“…There was also a linear negative correlation between the removal capacity of ACA-cactus formaldehyde from air ow and working time, with correlation coe cients greater than 0.91 (Table 1). It is well known that air ow rate and pollutant concentration are two important factors to control membrane diffusion, and effective working time is another key material performance index (Zha et al, 2024). In the orthogonal experiment, the formaldehyde concentration (Factor 1) was set at three levels as 0.081, 0.162 and 0.326 mg•m − 3 ;the air ow rate (Factor 2) was set at three levels as 0.5, 1.0 and 2.0 L•min − 1 while the working time (Factor 2) were set at three levels as 5, 10 and 30 h. Results showed that the rapid and highly e cient formaldehyde dissipation of plant active components in ACA-cactus made the air ow rate become the key factor on the removal rate with the sequence of Factor 2 > Factor 3 Factor 1.…”
Section: In Uencing Factors On Removal Ratementioning
confidence: 99%